2004
DOI: 10.1007/s10327-003-0113-4
|View full text |Cite
|
Sign up to set email alerts
|

Members of 14-3-3 protein isoforms interacting with the resistance gene product N and the elicitor of Tobacco mosaic virus

Abstract: A functional cDNA for the resistance gene N

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 46 publications
1
54
0
1
Order By: Relevance
“…S5). Previous studies have highlighted the role of 14-3-3 proteins during ETI (Konagaya et al, 2004;Yang et al, 2009;Oh et al, 2010;Oh and Martin, 2011). It is possible that HopQ1's virulence-promoting effect during ETI may be due to interfering with 14-3-3 proteins necessary for robust ETI signaling.…”
Section: Discussionmentioning
confidence: 99%
“…S5). Previous studies have highlighted the role of 14-3-3 proteins during ETI (Konagaya et al, 2004;Yang et al, 2009;Oh et al, 2010;Oh and Martin, 2011). It is possible that HopQ1's virulence-promoting effect during ETI may be due to interfering with 14-3-3 proteins necessary for robust ETI signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown that GF14 λ interacts with APX3 [70] and its over-expression in Arabidopsis increases drought stress tolerance [71]. Different 14-3-3 interacting proteins involved in response to stress or defense have been identified, which confer resistance to virus and fungal pathogens [72][73][74]. Recently, GF14 λ has been identified as a responsive phosphoprotein in a study on Arabidopsis proteome alterations upon P. syringae challenge [46].…”
Section: Methyl Viologen Treatmentmentioning
confidence: 99%
“…7 When BY2 cell lines are transformed with antisense constructs of Nt14-3-3h, the expression of the transgene is correlated with a strong inhibition of ROS accumulation following elicitation with cryptogein. This demonstrated the role of a 14-3-3 protein in the direct regulation of an oxidase during an incompatible interaction.…”
Section: Identification Of Regulators Of Plant Nadph Oxidasementioning
confidence: 99%